Evaluation of antimicrobial activity of aqueous extract, ethanol, methanol and ashes two species ramosissimum and telmateia of Equisetum arvense on several bacterial species and Yeast - Fatemeh Eslamiyan; Sadigheh Mehrabiyan; Ahmad Majd (Islamic Azad University, 2015)
Introduction: Bacterial infections are one of the major health challenges and authorities in this field are faced with many problems especially bacterial resistance to antibiotics. This study aimed to evaluate the antimicrobial effects of aqueous and alcoholic extracts and the ash of two species of horse tail herb against standard strains of Staphylococcus aureus, Escherichia coli and Candida albicans and investigate its effect on eukaryotic cells. Methods: Aqueous, methanolic and ethanolic extracts and ash were prepared from two horse tail species. In order to evaluate antibacterial function, well diffusion test was used by measuring inhibitory halo diameter on standard strains of Staphylococcus aureus, Candida albicans and E. coli. For determining the minimum inhibitory concentration (MIC) on these strains micro broth dilution method was applied. To evaluate its effect on the eukaryotic cells, blood agar medium was used. Results: Based on agar diffusion test, the halo of no bacterial growth was associated with extracts in different ranges in standard strains. The MIC was determined using the micro broth dilution. These extracts had no effects on red blood cells and did not produce hemolysis on blood agar medium. Conclusion: Horsetail extract can be used to treat fungal and bacterial infections either lonely or in combination with other antimicrobial agents. Due to its antimicrobial potential, it can especially be considered in the cases of drug resistance.